Metode User Centered Design (UCD) dalam Perancangan Aplikasi Manajemen Inventaris Tambang Laterite Berbasis Mobile - Saputra, Marwan Adi; Suhirman, Suhirman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The laterite mining business is a red rock mining activity or red deposits formed from the decomposition of various types of rocks. In running a laterite mining business, a lot of equipment is needed, such as transportation equipment and also the need for fuel and food for employees. Inventory recording needs to be done to avoid the risk of losing company assets. However, there is still a lot of damage to company asset data, this is because inventory recording is still manual using an inventory book. Data damage generally occurs due to human error, such as books that are accidentally torn or exposed to water while in the mining area. To overcome this, it is necessary to analyze and design an application technology that is able to store data safely and can also record inventory data efficiently. The research was conducted based on the problems that exist at CV. Anugrah Seruyan Raya which is located in Central Kalimantan. Designing an android-based laterite mine inventory management application that can record inventory and stock efficiently and can store data more securely so as to minimize the risk of loss or damage to company data. The application design was carried out using the user centered design (UCD) method and developed using the React Native programming language and MongoDB as the database. The resulting application is able to handle existing problems because the new system with the help of technology can make recording in the company more effective and efficient.